The ancient novel and beyond - Panayotakis, Stelios, 1968-; Zimmerman, M. (Maaike); Keulen, Wytse Hette (Leiden, Netherlands ; Boston : Brill, 2003)
This work comprises the revised versions of selected papers read at the International Conference on the Ancient Novel (Groningen, July 2000). The essays combine judicious use of literary theory with traditional scholarship, and examines the ancient novels and related texts.
Part One. The Ancient Novel in Context -- Alexander the Great in the Arabic Tradition / Richard Stoneman -- "The Last Days of Alexander" in an Arabic Popular Romance of Al-Iskandar / Faustina Doufikar-Aerts -- Lucius and Aesop Gain a Voice : Apul. Met. 11.1-2 and Vita Aesopi / Ellen Finkelpearl -- The Grand Vizier, the Prophet, and the Satirist : Transformations of the Oriental Ahiqar Romance in Ancient Prose Fiction / Marko Marincic -- Living Portraits and Sculpted Bodies in Chariton's Theater of Romance / Froma I. Zeitlin -- Spectator and Spectacle in Apuleius / Niall W. Slater -- Plato's Dream : Philosophy and Fiction in the Theaetetus / Kathryn Morgan -- Fiction as a Discourse of Philosophy in Lucian's Verae Historiae / Andrew Laird -- The Representation of Violence in the Greek Novels and Martyr Accounts / Cathryn Chew -- Three Death Scenes in Apollonius of Tyre / Stelios Panayotakis -- Part Two. The Ancient Novel in Focus -- Swordplay -- Wordplay : Phraseology of Fiction in Apuleius' Metamorphoses / Wytse Keulen -- Nymphs, Neighbours and Narrators : a Narratological Approach to Longus / John Morgan -- Reading for Pleasure : Narrative, Irony, and Eroticism in Achilles Tatius / Tim Whitmarsh -- The Winged Ass : Intertextuality and Narration in Apuleius' Metamorphoses / Luca Graverini -- Tlepolemus the Spectral Spouse / Donald Lateiner -- Epic Extremities : The Openings and Closures of Books in Apuleius' Metamorphoses / Stephen Harrison -- In mediis rebus : Beginning Again in the Middle of the Ancient Novel / Stephen Nimis -- La lettre dans le roman grec ou les liaisons dangereuses / Francoise Letoublon -- The Role of Inscriptions in Greco-Roman Novels / Erkki Sironen -- Strategies of Authentication in Ancient Popular Literature / William Hansen -- Part Three. Beyond the Ancient Novel -- Archaic Iambos and Greek Novel : A Possible Connection / Giuseppe Zanetto -- Resistant (and enabling) Reading : Petronius' Satyricon and Latin Love Elegy / Judith Hallett -- La mise en scene declamatoire chez les romanciers latins / Daneille van Mal-Maeder -- Der byzantinische Roman des 12. Jahrhunderts als Spiegel des zeitgenossischen Literaturbetriebs / Ruth Harder -- Static Imitation or Creative Transformation? : Achilles Tatius in Hysmine & Hysminias / Ingela Nilsson -- The "Entfuhrung aus dem Serail"-motif in the Byzantine (vernacular) Romances / Willem J. Aerts -- Staging the Fringe Before Shakespeare : Hans Sachs and the Ancient Novel / Niklas Holzberg -- Heliodor, Mademoiselle de Scudery und Umberto Eco : Lekturen des Liebesromans in L'isola del giorno prima / Gunter Berger -- From Petronius to Petrolio : Satyricon as a Model-Experimental Novel / Massimo Fusillo -- Myths of Person and Place : the Search for a Model for the Ancient Greek Novel / Gareth Schmeling.
Includes bibliographical references (pages 449-483) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Classical fiction -- History and criticism; Literature, Medieval -- Classical influences; Literature, Modern -- Classical influences; Roman ancien -- Histoire et critique; Littérature médiévale -- Influence ancienne; Littérature -- Influence grecque; TRAVEL -- Special Interest -- Literary; LITERARY CRITICISM -- General; Classical fiction; Literature, Medieval -- Classical influences; Literature, Modern -- Classical influences; Rezeption; Literatur; Roman; Romans; Klassieke talen; Klassieke oudheid; Literatura clássica (história e crítica); Groningen <2000>; Latein; Griechisch; Criticism, interpretation, etc